Problematika Pembelajaran Menulis dengan Metode Imla’ pada Santri Bimbingan Masuk Gontor (Bimago) - Khayyu Anggun Maharani; Fatkhurrahman Fatkhurrahman; Chairani Astina; Farah Faida (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
This study aims to analyze the problems and their solutions in learning to write using the IMLA method at BIMAGO. The research approach used is a qualitative case study method. Data collection was done by interview, observation, and documentation study. The data analysis process goes through three stages, namely data collection, data reduction, and data verification using frame analysis. The results of this study reveal that there are 5 problems that occur in BIMAGO, namely 1) students cannot yet distinguish various types of hijaiyah letters, 2) lack of student vocabulary, 3) new language for students, 4) difficulty understanding Arabic, and 5) lack of time in imla' learning. The factors that cause these problems are due to differences in family backgrounds, lack of student motivation, less conducive learning time and place, the inability of students to read the Koran, some students enter Bimago only to fill spare time due to the pandemic and the diversity of teaching dialects. The solution from the teacher's point of view is to give assignments, provide makhorijul letter material, foster motivation, and deliver material in a language that is easier for students to understand. The solution from the institutional side, BIMAGO held MABIT activities and carried out pre-test and post-test for students.